Interest of basic school students on mini volley balls - Murtiyono, Murtiyono; Kristiyanto, Agus; Doewes, Muchsin (Journal of Education, Health and Sport, 2019)
This study aims to find out what factors support the fifth grade students of SD Negeri Sragen Subdistrict in the learning process in mini volleyball games and how much these factors cause students of class V to take an interest in learning mini volleyball games. This type of research is descriptive research. This research includes survey research. The population in this study included the fifth grade students in the State Elementary School in Sragen Subdistrict, totaling 255 students. The research instrument uses a questionnaire or questionnaire. Data analysis used in this study uses quantitative descriptive statistics with percentages. The results of the study concluded that internal factors including physical, psychological and student and external levels of fatigue which included teachers, subject matter and infrastructure that supported the interest of mini volleyball learning in fifth grade elementary school students in Sragen sub-district were quite influential in supporting interest Class V students to learn mini volleyball.